E-041 Frailty predicts postoperative functional outcomes after microsurgical resection of ruptured brain arteriovenous malformations. (23rd July 2022) - Barros, G; Sen, R; McGrath, M; Nistal, D; Sekhar, L; Kim, L; Levitt, M
Abstract : Introduction: Frailty assessment has emerged as an important clinical variable to consider for predicting postoperative functional outcomes across surgical subspecialties, including neurosurgery. The purpose of this study was to determine the effectiveness of frailty, measured by the modified frailty index-5 (mFI-5), in predicting postoperative functional outcome after microsurgical resection of ruptured brain arteriovenous malformations (bAVMs). Methods: A retrospective database of patients undergoing microsurgical resection of acutely ruptured bAVMs was queried for patient demographics, bAVM characteristics and follow-up information, including mFI-5, ruptured arteriovenous malformation grading scale (RAGS), and Spetzler-Martin grade (S-M). The prognostic ability of mFI-5 in predicting postoperative functional outcome measured by modified Rankin scale (mRS) was assessed with univariate and multivariate logistic and linear regression analyses. The performance of RAGS and S-M alone was compared to adding mFI-5 with an area under the curve (AUC) analysis. Results: A total of 109 patients were included. In univariate analysis, for every 1-point increase in mFI-5, there was a statistically significant lower likelihood of good (mRS ≤ 2) functional outcome (OR 0.33, CI 0.15 - 0.60, p=0.011). Patients considered healthy with mFI-5 = 0 were significantly more likely to have a good postoperative outcome (OR 3.32, CI 1.24–8.97, p=0.017) than those considered frail with mFI-5 ≥ 1. In the multivariate analysis controlling for RAGS, for every 1-point increase in mFI-5, there was a corresponding significantly decreased likelihood of postoperative good functional outcome (OR 0.32, CI 0.14–0.63, p=0.0026), shown in Figure 1 . Conclusions: Measuring frailty with mFI-5 as an adjunct to established bAVM grading systems, such as the RAGS and S-M grade, could help assess a patient's individual likelihood of postoperative good functional outcome following ruptured bAVM resection better than either grading system alone. Disclosures: G. Barros: None. R. Sen: None. M. McGrath: None. D. Nistal: None. L. Sekhar: None. L. Kim: None. M. Levitt: 1; C; Medtronic, Stryker. 2; C; Medtronic, Metis Innovative. 4; C; Synchron, Cerebrotech, Proprio, Hyperion Surgical.